2015
DOI: 10.1111/jnc.13433
|View full text |Cite
|
Sign up to set email alerts
|

1,8‐ and 1,4‐cineole enhance spontaneous excitatory transmission by activating different types of transient receptor potential channels in the rat spinal substantia gelatinosa

Abstract: Although transient receptor potential (TRP) channels expressed in the spinal substantia gelatinosa play a role in modulating nociceptive transmission, their properties have not been fully examined yet. In order to address this issue, the effects of 1,8-cineole and its stereoisomer 1,4-cineole on excitatory transmission were examined by applying the wholecell patch-clamp technique to substantia gelatinosa neurons in adult rat spinal cord slices. Miniature excitatory postsynaptic current frequency was increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…59,71,79,80 It has also been reported that the substantia gelatinosa neurons in the presence of TRPV1 or TRPA1 or TRPM8 channels show a high degree of stereoselectivity and the high Hill coefficient of a dose response towards several classes of plant-derived menthol derivative chemical stereoisomers. They include thymol and carvacrol (C 10 H 14 O, 5-isopropyl-2-methylphenol), (À)-carvone (C 10 H 14 O, (À)-2-methyl- 71,[81][82][83][84][85] Therefore, it is promising to investigate if an H-bonded homochiral dimer or pair with side-or tandem-connected head-to-head or tail-totail or head-to-tail plays a pivotal role in discriminating stereoisomers for allosteric activation of those TRP channels.…”
Section: Cross-examination Of the Bimolecular-pushing "Gas Pedal" Model By Other Trp Channelsmentioning
confidence: 99%
“…59,71,79,80 It has also been reported that the substantia gelatinosa neurons in the presence of TRPV1 or TRPA1 or TRPM8 channels show a high degree of stereoselectivity and the high Hill coefficient of a dose response towards several classes of plant-derived menthol derivative chemical stereoisomers. They include thymol and carvacrol (C 10 H 14 O, 5-isopropyl-2-methylphenol), (À)-carvone (C 10 H 14 O, (À)-2-methyl- 71,[81][82][83][84][85] Therefore, it is promising to investigate if an H-bonded homochiral dimer or pair with side-or tandem-connected head-to-head or tail-totail or head-to-tail plays a pivotal role in discriminating stereoisomers for allosteric activation of those TRP channels.…”
Section: Cross-examination Of the Bimolecular-pushing "Gas Pedal" Model By Other Trp Channelsmentioning
confidence: 99%
“…‐Modulates TRP (transient receptor potential) channels (including increasing spontaneous glutamate release); dysregulation of which have been suggested to be involved in neurological and psychiatric disorders (Jiang et al, )…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
“…The SG neurons play a pivotal role in modulating nociceptive transmission from the periphery [ 24 , 25 , 26 ] and thus TRP channels in the SG are involved in its modulation. Their expressions in the SG have been shown by immunohistochemistry [ 27 ].…”
Section: Trp Channels Involved In Nociceptive Transmission Throughmentioning
confidence: 99%
“…The thymol activity was inhibited by a TRPA1 antagonist HC-030031 (50 μM; [ 95 ]) but not a TRPV1 antagonist capsazepine (10 μM; [ 96 ]) and a TRPM8 antagonist (4-(3-chloro-2-pyridinyl)- N -[4-(1,1-dimethyl-ethyl)phenyl]-1-piperazinecarboxamide, BCTC, 3 μM; [ 97 ]; Figure 1 E). BCTC at this concentration was effective in inhibiting sEPSC frequency increase produced by menthol in adult rat SG neurons [ 27 ]. As with thymol, the carvacrol activity was resistant to capsazepine (10 μM) while being depressed by HC-030031 (50 μM; Figure 1 F).…”
Section: Actions Of Plant-derived Stereoisomers On Spontaneous Excmentioning
confidence: 99%
See 1 more Smart Citation